Demonstration and experiment on archaebacteria and eubacteria: effectiveness for cognitive learning outcomes (CLO) based on critical thinking skill - Muhammad Hamdani; Baskoro Adi Prayitno; Puguh Karyanto (Biosfer: Jurnal Pendidikan Biologi, 2020)
The purpose of this study was to determine differences in students' cognitive learning outcomes (CLO) using demonstration and experimental learning methods. The Clo differences are in students who have high critical thinking skills (HCTS) and low critical thinking skills (LCTS), and whether there is or not the interaction between learning methods and critical thinking towards students CLO. Hopefully, this research could strengthen existing theories and inform other teacher colleagues by using demonstration and experimentation methods in other subjects to improve the quality of a school. The study design used a 2 x 2 factorial design. The study population was students of X science class in one of the state high schools in Central Lombok, Indonesia, which amounted to 18 schools. The study sample amounted to 2 schools. In order to select the research sample, we used purposive random sampling. CLO and critical thinking skills were measured by using essay tests.esting on the validity and reliability of CLO tests and critical thinking skill showed valid and reliable results. Data were analyzed using ANCOVA with pre-test scores as covariates. The results showed that there were significant differences in CLO between students learning to use the demonstration and experimental learning method. There was a significant difference in CLO between students who have HCTS and LCTS, and there was no interaction between learning methods and critical thinking on student’s CLO. Experimental method learning is more optimal to improving student CLO when When it is applied to HCTS students rather than LCTS students on Archaebacteria and Eubacteria.